Study of Factors Influencing Knowledge, Attitude and Practice on Village-Drug-Co-Operatives of Nakornpathom People - Chalongsuk, Rapeepun; Nunthanish, Jurairat (Journal of Health Science of Thailand, 1995)
Factors influencing knowledge, attitude and practice on village-drug-co-operatives of Nakornpathom people were studied from 680 random samples of Maung and Kampangsan districts. All samples were familiar with village-drug-co-operatives. Education level, occupation, income and money saving are factors which influence knowledge, attitude and practice on villagedrug-co-operatives of Nakornpathom people. Prathomsuksa (primary education level) group(83.54%), cultivator group(60.30%), middle income and no saving group(54.56%) have better score in knowledge, attitude and practice on village-drug-co-operatives than other groups. Although the high education level group, high income and saving group have higher score in knowledge concerning health, they have less score in knowledge, attitude and practice on villagedrug-co-operatives. Knowledge on village-drug-co-operatives have direct and indirect effects on attitude and practice on village-drug-co-operatives among most study groups. Among labor group and no saving group, there are no indirect effects due to other factors such as business benefits and debt. In the high education level group and government official group, there are neither direct nor indirect effects of knowledge on village-drug-co-operatives.